GAMBARAN FEAR OF CRIME YANG DIALAMI PARA PENGEMUDI KETIKA MELINTASI TRANS SUMATERA DI PROVINSI LAMPUNG - Fahmi, Teuku (JURNAL SOSIOLOGI, 2013)
The aims of this research were to identified and described the fear of crime level differentiation among goods transport drivers and private vehicle drivers when they crossed the Trans Sumatra, Lampung Province. This research was also clarified the mechanism of coping (adjustment) to the fear of crime level between goods transport drivers and private vehicle drivers through the journey crossed the Trans Sumatera, Lampung Province. This research used a quantitative approach, meanwhile the type of the research was explanative. The total number of respondents were 200 people. Related to the result of different test calculation, there was a significant fear of crime rate differentiation between freight drivers and private vehicle drivers. In this case the freight drivers have higher average rank for the fear of crime rate compared to the private vehicle drivers.Â Keywords: perceived risk, fear of crime, coping strategies